Sizing agent and preparation method thereof, sized carbon fiber and carbon fiber composite material

By using a sizing agent composed of flame retardant epoxy resin emulsion, polyvinyl alcohol aqueous solution, modified nano silica sol and curing agent in the carbon fiber composite, the problem of degradation of material performance in the prior art caused by the addition of flame retardant in the prior art is solved, and a carbon fiber composite material with high flame retardancy and excellent mechanical properties is achieved.

CN119531136APending Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311103288.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When existing carbon fiber composites improve flame retardant properties, the commonly used method is to add flame retardant, but this will lead to a decrease in the mechanical and thermodynamic properties of the resin, affecting the overall performance of the material.

Method used

A sizing agent of an epoxy resin-based carbon fiber composite material is used, which consists of a flame-retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, a modified nanosilica sol and a curing agent. Through synergistic action, the binding and cross-linking effect of carbon fiber and flame-retardant epoxy resin are significantly improved.

Benefits of technology

It significantly improves the flame retardant properties and mechanical properties of carbon fiber composite materials, ensures the high oxygen index, strong interlayer shear strength and good tensile properties of the material, while ensuring the stability and easy storage of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004421260900000141
    Figure BDA0004421260900000141
Patent Text Reader

Abstract

The invention relates to the field of carbon fiber composite materials, and discloses a sizing agent and a preparation method thereof, sizing carbon fibers and a carbon fiber composite material. The sizing agent comprises a flame-retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, modified nano silicon dioxide sol and a curing agent. The sizing agent can significantly improve the flame retardant property of a carbon fiber composite material, improve the bonding property of flame-retardant epoxy resin and a carbon fiber sizing interface, and overcome the defect that the bonding property of flame-retardant epoxy resin and carbon fibers is poor due to the addition of a flame retardant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of carbon fiber composite materials, and in particular to a sizing agent and a preparation method thereof, sized carbon fibers and carbon fiber composite materials. Background Art

[0002] Carbon fiber composite materials have the advantages of low density, corrosion resistance, high temperature resistance, good mechanical properties, high elastic modulus and convenient construction, and their application demand is becoming more and more extensive. In the fields of transportation, construction, electronic appliances, etc., carbon fiber also has incomparable advantages, but these fields have high requirements for the flame retardant properties of materials, and the matrix resin epoxy resin commonly used in composite materials is one of the more flammable thermosetting resins. The oxygen index of ordinary epoxy resin is only about 19.8%, and it will continue to burn after the fire source is evacuated, increasing the risk of fire. The current common method to improve the flame retardant properties of composite materials is to prepare epoxy resins with flame retardant properties. The main technical approach is to add flame retardants to the epoxy resin system, but the flame retardant efficiency of commonly used environmentally friendly halogen-free flame retardants is relatively low. In order to achieve a certain flame retardant performance, it is necessary to increase the amount of flame retardant, which seriously affects the mechanical and thermodynamic properties of the resin and thus affects the performance of the composite material.

[0003] The sizing agent used for carbon fiber is often epoxy resin sizing agent, which also increases the risk of material combustion. Currently, there are more flame retardant modifications for epoxy resin, but there are fewer sizing systems for carbon fiber. The commonly reported method is to add a single flame retardant, which does not significantly improve the flame retardancy of carbon fiber, and does not fully consider the bonding between carbon fiber and flame retardant resin after sizing and the mechanical properties of the subsequent composite material. Adding flame retardants to the epoxy resin system will result in poor bonding between epoxy resin and carbon fiber.

[0004] Therefore, in order to reduce the problem of reduced mechanical properties of composite materials caused by excessive addition of flame retardants to the matrix resin and poor resin processability during composite material molding, it is of great significance to introduce flame retardant elements in the form of sizing agent modification to improve the flame retardant properties of carbon fiber composites, thereby optimizing the connection interface between carbon fiber and resin and improving the mechanical properties of composite materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of poor bonding between epoxy resin and carbon fiber due to the addition of flame retardant in the flame retardant epoxy resin in the prior art, and provide a sizing agent and a preparation method thereof, sized carbon fiber and carbon fiber composite material. The sizing agent can significantly improve the cross-linking effect of the flame retardant epoxy resin and the carbon fiber sizing interface, improve the flame retardant properties of the carbon fiber composite material, and strengthen the bonding effect between the epoxy resin and the carbon fiber.

[0006] In order to achieve the above object, the first aspect of the present invention provides an epoxy resin-based carbon fiber composite material sizing agent, the sizing agent comprising a flame retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, a modified nano-silica sol and a curing agent.

[0007] The second aspect of the present invention provides a method for preparing an epoxy resin-based carbon fiber composite material sizing agent, the method comprising mixing a flame retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, a modified nano-silica sol and a curing agent, and first stirring to obtain the sizing agent.

[0008] The third aspect of the present invention provides a sized carbon fiber, wherein the sized carbon fiber contains the sizing agent described in the first aspect of the present invention or the sizing agent prepared by the method described in the second aspect.

[0009] A fourth aspect of the present invention provides a carbon fiber composite material, wherein the composite material comprises the carbon fiber described in the third aspect of the present invention and a flame retardant resin.

[0010] Through the above technical solution, the present invention mainly has the following beneficial effects:

[0011] (1) The sizing agent provided by the present invention is a water-based sizing agent. On the one hand, it is suitable for sizing large-tow carbon fibers (the number of carbon fibers in each bundle is greater than 48,000 (abbreviated as 48K)), has high matching and uniform sizing, and can improve the flame retardant properties of carbon fibers. On the other hand, it is suitable for use in flame-retardant epoxy resin-based carbon fiber composites, and can significantly improve the cross-linking effect between the flame-retardant epoxy resin and the carbon fiber sizing interface. While improving the flame retardant properties of the carbon fibers, the bonding effect between the epoxy resin and the carbon fibers is stronger, so that the performance of the prepared composite materials is excellent.

[0012] (2) In the sizing agent provided by the present invention, the flame retardant epoxy resin emulsion and the curing agent have a synergistic effect, which can improve the curing activity and promote the cross-linking of the flame retardant epoxy resin and the carbon fiber sizing interface. The flame retardant epoxy resin emulsion, polyvinyl alcohol aqueous solution, nano-silicon dioxide silica sol and curing agent work together to highly match the large-tow carbon fiber. When the flame retardant is added, a high flame retardant activity is still guaranteed, and a flame retardant epoxy resin-based carbon fiber composite material with excellent properties is obtained.

[0013] (3) The preparation method of the sizing agent provided by the present invention has readily available raw materials, low cost, simple operation, and is environmentally friendly and safe; the prepared sizing agent system is stable, easy to store, and has strong applicability.

[0014] (4) The carbon fiber composite material sized with the sizing agent provided by the present invention has an oxygen index of not less than 35%, an interlaminar shear strength of not less than 74 MPa, and a tensile property of not less than 1900 MPa. DETAILED DESCRIPTION

[0015] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0016] A first aspect of the present invention provides an epoxy resin-based carbon fiber composite material sizing agent, the sizing agent comprising a flame retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, a modified nano-silica sol and a curing agent.

[0017] The sizing agent provided by the present invention has synergistic effects among various components, which can promote the cross-linking of the interface between the flame-retardant epoxy resin and the carbon fiber sizing while improving the flame retardancy of the sizing agent. The epoxy resin and the carbon fiber have a stronger bonding effect, further improving the mechanical properties of the carbon fiber composite material.

[0018] According to the present invention, the mass ratio of the flame retardant epoxy resin emulsion, the polyvinyl alcohol aqueous solution, the modified nano-silica sol and the curing agent is (40-70):(3-15):(3-10):(20-40), preferably (55-65):(5-8):(5-8):(25-35).

[0019] The inventors found in their research that when the mass ratio of flame retardant epoxy resin emulsion, polyvinyl alcohol aqueous solution, modified nano-silica sol and curing agent meets the following conditions: (40-70): (3-15): (3-10): (20-40), the carbon fiber sized with the prepared sizing agent reduces the combustion risk of the carbon fiber material, and the bonding force between the carbon fiber and the flame retardant epoxy resin is stronger. In some embodiments of the present invention, the interlaminar shear strength of the carbon fiber composite material after sizing can reach at least 74 MPa.

[0020] When the mass ratio of the flame-retardant epoxy resin emulsion, the polyvinyl alcohol aqueous solution, the modified nano-silica sol and the curing agent is within the preferred range of (40-70):(3-15):(3-10):(20-40), the carbon fiber sized with the prepared sizing agent has better flame retardant properties and mechanical properties.

[0021] According to the present invention, the flame retardant epoxy resin emulsion comprises epoxy resin, flame retardant, anhydrous ethanol and water; preferably, the mass ratio of the epoxy resin, flame retardant, anhydrous ethanol and water is 5:(1-4):(25-50):(25-100).

[0022] In the present invention, the main function of the flame retardant epoxy resin emulsion is to improve the flame retardant properties of the sizing agent. When the mass ratio of epoxy resin, flame retardant, anhydrous ethanol and water is 5:(1-4):(25-50):(25-100), the obtained flame retardant epoxy resin emulsion has the best performance.

[0023] According to the present invention, the epoxy equivalent of the epoxy resin is 100-250 g / eq., and the viscosity at 25° C. is 1500-20000 mPa·s.

[0024] According to the present invention, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.

[0025] In a particularly preferred embodiment of the present invention, the epoxy resin includes E51 epoxy resin and R170 epoxy resin, the mass ratio of E51 epoxy resin to R170 epoxy resin is 1-4:1-4, preferably, the sum of the mass ratios of E51 epoxy resin and R170 epoxy resin is 5, for example: 4:1, 3:2, 1:4, 2:3.

[0026] In one embodiment of the present invention, the epoxy equivalent of E51 epoxy resin is 110-230 g / eq., and the viscosity at 25° C. is 11000-14000 mPa·s.

[0027] In one embodiment of the present invention, the epoxy equivalent of R170 epoxy resin is 170-190 g / eq., and the viscosity at 25° C. is 2000-5000 mPa·s.

[0028] According to the present invention, the flame retardant is a halogen-free flame retardant.

[0029] According to the present invention, the flame retardant is selected from at least one of phosphazene flame retardants, alkyl phosphinates, phosphaphenants, phosphate esters, phosphates, organosilicon compounds, metal oxides, metal hydroxides and graphite substances.

[0030] Further, the flame retardant is preferably selected from at least one of ammonium hydrogen phosphate, ammonium polyphosphate, boric acid, ammonium molybdate, polydiphenoxyphosphazene, hexaphenoxycyclotriphosphazene, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, phosphaphenanthrene triazine compound, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, triphenyl phosphate, resorcinol bis(diphenyl) phosphate, and toluene diphenyl phosphate.

[0031] In the present invention, hexaphenoxy cyclotriphosphazene, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, triphenyl phosphate, resorcinol bis(diphenyl) phosphate, and toluene diphenyl phosphate are fat-soluble flame retardants.

[0032] In the present invention, ammonium hydrogen phosphate, ammonium polyphosphate, boric acid and ammonium molybdate are water-soluble flame retardants.

[0033] In the present invention, the inventors have found through research that the flame retardant is selected from at least two of the above, and when added in steps, the synergistic effect of the flame retardant and other components in the sizing agent can be maximized, the flame retardant properties can be fully exerted, and at the same time, the mechanical properties can be ensured not to decrease.

[0034] According to the present invention, the mass ratio of polyvinyl alcohol to water contained in the polyvinyl alcohol aqueous solution is 1:(20-50).

[0035] In the present invention, the role of the polyvinyl alcohol aqueous solution is to improve the dispersibility and stability of the sizing agent polymerization system.

[0036] According to the present invention, the curing agent is selected from at least one of modified imidazole, aromatic amine curing agent and aliphatic amine curing agent.

[0037] In the present invention, the inventor has found through research that the type and amount of curing agent directly affect the curing speed and the performance of the cured product. By selecting the appropriate type and amount of curing agent, the curing time of the sizing agent and the performance of the cured product can be controlled to meet the processing requirements. For the present invention, the curing agent preferably uses modified imidazole to better enhance the curing effect, improve the performance of the epoxy sizing agent, improve the sizing quality and processing efficiency, and simplify the processing process and reduce costs. At the same time, it can react chemically with epoxy resin, promote the curing process of the sizing agent, improve the hardness and wear resistance of the cured film, improve the strength and durability of the sizing, thereby improving the quality and processing efficiency of the back-end products.

[0038] According to a particularly preferred embodiment of the present invention, the modified imidazole is diethyltetramethylimidazole.

[0039] In the present invention, the modified nano-silicon dioxide can enhance the adhesion of the sizing agent on the surface of the carbon fiber, and produce good chemical bonding with the epoxy sizing agent, thereby significantly enhancing the adhesion of the epoxy sizing agent on the surface of the fabric, improving the sizing effect and the anti-sizing performance of the fabric. At the same time, the wear resistance and wrinkle resistance of the sized carbon fiber are improved, thereby improving the service life and appearance quality of the fabric.

[0040] A second aspect of the present invention provides a method for preparing an epoxy resin-based carbon fiber composite material sizing agent, characterized in that the method comprises mixing a flame retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, a modified nano-silica sol and a curing agent and then performing a first stirring to obtain the sizing agent.

[0041] The preparation method of the sizing agent provided by the invention is simple to operate and is environmentally friendly and safe.

[0042] According to the present invention, the first stirring conditions include a stirring temperature of 80-120° C., a stirring time of 1-3 h, and a stirring rate of 200-500 rpm.

[0043] In the present invention, the first stirring is performed in a thermostatic reactor. To achieve uniform mixing of the raw materials, the stirring temperature is 80-120°C, the stirring time is 1-3h, and the stirring rate is 200-500rpm. If the stirring temperature is too low, the mixing cannot be uniform; if the stirring temperature is too high, the product will be denatured; if the stirring time is too short, the mixing cannot be uniform; if the stirring time is too long, the preparation efficiency will be reduced; if the stirring rate is too fast, too many bubbles will be introduced; if the stirring rate is too slow, the mixing cannot be uniform.

[0044] According to the present invention, the method for preparing the flame retardant epoxy resin emulsion comprises: uniformly mixing epoxy resin, flame retardant, anhydrous ethanol and water to obtain the flame retardant epoxy resin emulsion.

[0045] In the present invention, the mixing may be a conventional mixing method, such as physical mixing.

[0046] According to a preferred embodiment of the present invention, the epoxy resin includes E51 epoxy resin and R170 epoxy resin, and the mass ratio of the E51 epoxy resin to the R170 epoxy resin is 1-4:1-4.

[0047] According to the present invention, the mass ratio of the epoxy resin to the flame retardant is 5:1-4.

[0048] In the present invention, the inventors have found through research that when the mass ratio of the epoxy resin to the flame retardant satisfies the above range, the sizing agent can be applied to carbon fiber without reducing its mechanical properties.

[0049] Furthermore, the mass ratio of the epoxy resin to the flame retardant is 5:2-3.

[0050] According to the present invention, the mass ratio of the epoxy resin to anhydrous ethanol is 1:5-10.

[0051] According to the present invention, the mass ratio of the epoxy resin to water is 1:5-20.

[0052] In a specific embodiment of the present invention, the preparation method of the flame retardant epoxy resin emulsion comprises: preparing E51 epoxy resin, R170 epoxy resin, hexaphenoxy cyclotriphosphazene and anhydrous ethanol respectively in a mass ratio of 4:1:1:30, stirring and dissolving the E51 epoxy resin, R170 epoxy resin and hexaphenoxy cyclotriphosphazene at 80-100°C; simultaneously dissolving ammonium polyphosphate in water in a mass ratio of flame retardant to water of 1:25, and then mixing the flame retardant epoxy resin, anhydrous ethanol and aqueous solution, wherein the mass of water is 10 times the total mass of E51 epoxy resin and R170 epoxy resin, to obtain epoxy resin emulsion.

[0053] According to the present invention, the preparation method of the modified nano-silica sol comprises:

[0054] (1) mixing ethyl orthosilicate and ethanol uniformly, stirring and drying to obtain nano silicon dioxide powder;

[0055] (2) The nano-silica powder and ethanol are uniformly mixed, a silane coupling agent is added, and the mixture is stirred for a third time to obtain a modified nano-silica sol.

[0056] In the present invention, after the step (1) of uniformly mixing tetraethyl orthosilicate and ethanol, the step further comprises adjusting the pH of the solution to 7.5-10.

[0057] According to the present invention, in step (1), the mass ratio of ethyl orthosilicate to ethanol is 1:8-15.

[0058] According to the present invention, the second stirring conditions include: stirring temperature of 20-80° C., stirring time of 0.1-8 h, and stirring rate of 100-500 rpm.

[0059] According to the present invention, the mass ratio of the nano-silicon dioxide powder, ethanol and silane coupling agent in step (2) is 1: (8-15): (0.01-0.1).

[0060] According to the present invention, the third stirring conditions include: stirring temperature of 20-80° C., stirring time of 0.1-8 h, and stirring rate of 100-500 rpm.

[0061] According to the present invention, the silane coupling agent in step (2) is selected from at least one of KH550, KH560 and KH570.

[0062] In the present invention, the addition of the silane coupling agent can adjust the solution dispersibility and uniformity of the modified nano-silica sol, and further improve the stability of the sizing agent and the performance of subsequent applications.

[0063] In one embodiment of the present invention, the preparation method of the modified nano-silica sol comprises: stirring ethyl orthosilicate and ethanol at a mass ratio of 1:10, adjusting the pH to 7.5-10, heating and stirring at 20-80°C for 1 hour, centrifuging and washing, and drying to obtain nano-silica powder; stirring the nano-silica powder and ethanol at a mass ratio of 1:8, adding silane coupling agent KH550, heating and stirring at 50°C for 1 hour, and after centrifugal washing, dripping 8 times the mass of the solid silicon compound of water to obtain modified nano-silica silica sol.

[0064] The third aspect of the present invention provides a sized carbon fiber, wherein the sized carbon fiber contains the sizing agent described in the first aspect of the present invention or the sizing agent prepared by the method described in the second aspect.

[0065] A fourth aspect of the present invention provides a carbon fiber composite material, wherein the composite material comprises the carbon fiber described in the third aspect of the present invention and a flame retardant resin.

[0066] According to a preferred embodiment of the present invention, the flame retardant resin is prepared by mixing epoxy resin, a curing agent, an accelerator, a flame retardant, a diluent, a defoaming agent and a coupling agent and then curing the mixture.

[0067] The present invention will be described in detail below through examples.

[0068] In the following embodiments, the carbon fiber is selected from Shanghai Petrochemical SCF35S-48K polyacrylonitrile-based carbon fiber.

[0069] In the following embodiments, the method for sizing carbon fiber with the prepared sizing agent includes: pouring the sizing agent prepared by the present invention into the sizing tank of the sizing system of the Shanghai Petrochemical carbon fiber production line, completing the sizing process of the surface treated and dried carbon fiber, wherein the sizing residence time is 10-60 seconds, and then drying, the drying temperature is 80-250°C, to obtain the carbon fiber sized with the sizing agent.

[0070] In the following embodiments, a molding method of sizing carbon fiber and homemade flame retardant epoxy resin is also provided, and the method of use includes: vacuum degassing the self-developed flame retardant epoxy resin at 50°C, placing the resin into the resin tank of the winding machine, and winding it with Shanghai Petrochemical 48 large tow carbon fiber. The composite material curing process is 120 minutes at 90°C and then 120 minutes at 140°C.

[0071] Wherein, the flame retardant epoxy resin is prepared according to the following method:

[0072] (1) 35 wt % of epoxy resin and 8 wt % of diluent were uniformly mixed, and 20.5 wt % of flame retardant and 0.2 wt % of defoamer were added to obtain a mixture I;

[0073] (2) 3.8 wt% of coupling agent, 31 wt% of curing agent and 1.5 wt% of accelerator are added to the mixture I, mixed evenly and cured to obtain a flame retardant epoxy resin. The curing conditions are: keeping the temperature at 100° C. for 120 min until the resin gels, then raising the temperature to 140° C. and continuing the reaction for 180 min.

[0074] Wherein, the epoxy resin, curing agent, accelerator, flame retardant, diluent, coupling agent and defoaming agent are all commercially available.

[0075] In the following examples and comparative examples, the epoxy equivalent of the E51 epoxy resin is 110-230 g / eq., and the viscosity is 1500-10000 mPa·s; the epoxy equivalent of the R170 epoxy resin is 170-190 g / eq., and the viscosity is 2000-5000 mPa·s;

[0076] Modified imidazole, diethyltetramethylimidazole;

[0077] Oxygen index measurement is in accordance with national standard GB / T 2406;

[0078] The tensile properties of composite materials are measured according to the national standard GB / T 3354;

[0079] The measurement of composite material layer shear performance is in accordance with the national standard GB / T 3357.

[0080] Example 1

[0081] (1) Prepare 4g of E51 epoxy resin, 1g of R170 epoxy resin, 1g of hexaphenoxy cyclotriphosphazene and 30g of anhydrous ethanol respectively, with a mass ratio of 4:1:1:30. Stir and dissolve E51 epoxy resin, R170 epoxy resin and hexaphenoxy cyclotriphosphazene at 80-100°C to obtain mixture I; dissolve 1g of ammonium polyphosphate in 50g of water to obtain mixture II. Then, the above mixtures I and II are mixed, and the mass of water is 10 times the total mass of E51 epoxy resin and R170 epoxy resin to obtain a flame retardant epoxy resin emulsion.

[0082] (2) Mix 1 g of polyvinyl alcohol with 50 g of water, heat and stir until uniform, and obtain a polyvinyl alcohol solution.

[0083] (3) After 1 g of tetraethyl orthosilicate and 10 g of ethanol are mixed at a mass ratio of 1:10, the pH is adjusted to 7.5, the mixture is heated and stirred at 60° C. for 1 hour, and the mixture is centrifuged, washed, and dried to obtain nano-silicon dioxide powder. After 1 g of the nano-silicon dioxide powder and 8 g of ethanol are mixed at a mass ratio of 1:8, 0.1 g of silane coupling agent KH550 is added, and the mixture is heated and stirred at 50° C. for 1 hour to obtain a solid silicon compound. After centrifugal washing, water 8 times the mass of the solid silicon compound is added dropwise to obtain a modified nano-silicon dioxide silica sol.

[0084] (4) According to weight, 43 g of flame-retardant epoxy resin emulsion, 15 g of polyvinyl alcohol, 10 g of modified nano-silica sol, and 32 g of modified imidazole are added in sequence to a constant temperature stirring kettle and stirred evenly to obtain the desired sizing agent.

[0085] (5) The sizing agent is poured into the sizing tank of the sizing system of the carbon fiber production line, the surface-treated carbon fiber is fully soaked in the sizing agent for 20 seconds, and then dried to obtain the carbon fiber sized with the special sizing agent for flame-retardant epoxy resin-based carbon fiber composite materials.

[0086] (6) The carbon fiber is wound into a Noel ring and then cured.

[0087] Example 2

[0088] (1) 3 g of E51 epoxy resin, 2 g of R170 epoxy resin, 1 g of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphorylphenanthrene-10-oxide (ODOPB) and 50 g of anhydrous ethanol were prepared in a mass ratio of 3:2:1:50, and the E51 epoxy resin, R170 epoxy resin and ODOPB were stirred and dissolved at 150-180° C. to obtain a mixture I; 3 g of ammonium hydrogen phosphate was dissolved in 100 g of water to obtain a mixture II, and then the above mixture I and mixture II were mixed to obtain a flame retardant epoxy resin emulsion.

[0089] (2) Mix 1 g of polyvinyl alcohol with 40 g of water, heat and stir until uniform, and obtain a polyvinyl alcohol solution.

[0090] (3) The preparation of modified nano-silica silica sol is consistent with Example 1.

[0091] (4) Add 50 g of flame-retardant epoxy resin emulsion, 10 g of polyvinyl alcohol, 10 g of modified nano-silica sol, and 30 g of modified imidazole, in parts by weight, to a constant temperature stirring kettle and stir evenly to obtain the desired sizing agent.

[0092] (5) pouring the sizing agent into the sizing tank of the sizing system of the carbon fiber production line, fully soaking the surface-treated carbon fiber in the sizing agent for 20 seconds, and then drying it to obtain the carbon fiber sized with the special sizing agent for flame-retardant epoxy resin-based carbon fiber composite materials.

[0093] The carbon fiber and the homemade flame-retardant epoxy resin were Noel ring-wound and cured.

[0094] Example 3

[0095] (1) 1 g of E51 epoxy resin, 4 g of R170 epoxy resin, 1 g of resorcinol bis(diphenyl) phosphate and 60 g of anhydrous ethanol are prepared respectively in a mass ratio of 1:4:1:60, and the E51 epoxy resin, R170 epoxy resin and resorcinol bis(diphenyl) phosphate are stirred and dissolved at 80-100° C. to obtain a mixture I; 1 g of boric acid and 1 g of ammonium molybdate are dissolved in 80 g of water to obtain a mixture II, and the mass ratio of boric acid:ammonium molybdate:water is 1:1:80. Subsequently, the above mixture I and mixture II are mixed to obtain a flame retardant epoxy resin emulsion.

[0096] (2) Mix 1 g of polyvinyl alcohol with 30 g of water, heat and stir until uniform, and obtain a polyvinyl alcohol solution.

[0097] (3) After 1 g of tetraethyl orthosilicate and 10 g of ethanol are stirred evenly, the pH is adjusted to 7.5, heated and stirred at 60° C. for 1 hour, centrifuged and washed, and the centrifuged product is dried to obtain nano-silicon dioxide powder; after the nano-silicon dioxide powder and ethanol are stirred evenly at a mass ratio of 1:10, 0.1 g of silane coupling agent KH550 is added, and the solid silicon compound is heated and stirred at 60° C. for 1 hour to obtain a solid silicon compound, and after centrifugation and washing, distilled water is slowly added dropwise, and the mass of the distilled water is 8 times the mass of the solid silicon compound to obtain a modified nano-silicon dioxide sol.

[0098] (4) According to weight, 60 g of flame retardant epoxy resin emulsion, 7 g of polyvinyl alcohol, 7 g of modified nano-silica sol, and 26 g of modified imidazole are added to a constant temperature stirring kettle in sequence and stirred evenly to obtain the desired sizing agent.

[0099] (5) The sizing agent is poured into the sizing tank of the sizing system of the carbon fiber production line, the surface-treated carbon fiber is fully soaked in the sizing agent for 20 seconds, and then dried to obtain a carbon fiber sized with a special sizing agent for flame-retardant epoxy resin-based carbon fiber composite materials.

[0100] (6) The carbon fiber and the self-made flame-retardant epoxy resin are Noel ring-wound and cured.

[0101] Example 4

[0102] (1) 2 g of E51 epoxy resin, 3 g of R170 epoxy resin, 0.8 g of hexaphenoxy cyclotriphosphazene, 0.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 65 g of anhydrous ethanol were prepared respectively, and the mass ratio thereof was 2:3:0.8:0.2:65. The E51 epoxy resin, R170 epoxy resin, hexaphenoxy cyclotriphosphazene and DOPO were stirred and dissolved at 100-120° C. to obtain a mixture I; 1 g of ammonium polyphosphate and 1 g of ammonium molybdate were dissolved in 100 g of water to obtain a mixture II, and the mass ratio of ammonium polyphosphate:ammonium molybdate:water was 1:1:100. Subsequently, the above mixture I and mixture II were mixed to obtain a flame retardant epoxy resin emulsion.

[0103] (2) Mix polyvinyl alcohol and water in a mass ratio of 1:20, heat and stir until uniform, and obtain a polyvinyl alcohol solution.

[0104] (3) The preparation of modified nano-silica sol is consistent with that in Example 3;

[0105] (4) Add 65 g of epoxy resin emulsion, 5 g of polyvinyl alcohol, 5 g of nano-silica silica sol, and 25 g of modified imidazole in a constant temperature stirring kettle in sequence, and stir evenly to obtain the desired sizing agent.

[0106] (5) The sizing agent is poured into the sizing tank of the sizing system of the carbon fiber production line, the surface-treated carbon fiber is fully soaked in the sizing agent for 20 seconds, and then dried to obtain a carbon fiber sized with a special sizing agent for flame-retardant epoxy resin-based carbon fiber composite materials.

[0107] (6) The carbon fiber and the self-made flame-retardant epoxy resin are Noel ring-wound and cured.

[0108] Example 5

[0109] The method of Example 4 is followed, except that the amount of hexaphenoxycyclotriphosphazene used is 0.8 g, DOPO is not included, and the amount of ammonium polyphosphate used is 0.2 g, and ammonium molybdate is not included.

[0110] Example 6

[0111] The method of Example 4 is followed, except that the flame retardant is only 3 g of hexaphenoxy cyclotriphosphazene, and no other flame retardants are included.

[0112] Example 7

[0113] The method of Example 4 is followed, except that the amount of hexaphenoxycyclotriphosphazene used is 2.8 g, and other factors remain unchanged.

[0114] Comparative Example 1

[0115] (1) Use common purchased epoxy resin emulsion sizing agent to sizing carbon fiber.

[0116] (2) The sizing agent is poured into the sizing tank of the sizing system of the carbon fiber production line, the surface-treated carbon fiber is fully soaked in the sizing agent for 20 seconds, and then dried to obtain an epoxy resin-based carbon fiber.

[0117] (3) The carbon fiber and the self-made flame-retardant epoxy resin are Noel ring-wound and cured.

[0118] Comparative Example 2

[0119] The method of Example 4 was followed, except that no flame retardant was included.

[0120] Test Case

[0121] The sizing rate of the sizing carbon fibers in the embodiment and the comparative example was tested; the mechanical property test and oxygen index test of the carbon fiber composite materials in the embodiment and the comparative example 1 were performed. The test results are shown in Table 1.

[0122] Table 1

[0123]

[0124] It can be seen from the results in Table 1 that the carbon fiber composite material sized with the sizing agent provided by the present invention has high interlaminar shear strength and tensile properties, and has a high oxygen index and excellent flame retardant properties. While ensuring the sizing rate, the flame retardant properties of the carbon fiber composite material can be effectively improved, and the bonding with the matrix epoxy resin can be ensured, and the obtained composite material has high mechanical properties.

[0125] In Comparative Example 1, since the purchased epoxy resin emulsion sizing agent is different from the component formula of the present invention, not only the oxygen index is reduced, but also the interlaminar shear strength and tensile properties are slightly worse. This indirectly illustrates that the sizing agent provided by the present invention can improve the flame retardant properties of carbon fiber composite materials while not reducing or even slightly improving their tensile properties and interlaminar shear strength.

[0126] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A sizing agent, characterized in that The sizing agent comprises flame retardant epoxy resin emulsion, polyvinyl alcohol aqueous solution, modified nano silica sol and curing agent.

2. The sizing agent according to claim 1, characterized in that The mass ratio of the flame retardant epoxy resin emulsion, the polyvinyl alcohol aqueous solution, the modified nano-silica sol and the curing agent is (40-70):(3-15):(3-10):(20-40), preferably (55-65):(5-8):(5-8):(25-35).

3. The sizing agent according to claim 1 or 2, characterized in that The flame retardant epoxy resin emulsion comprises epoxy resin, flame retardant, anhydrous ethanol and water; Preferably, the mass ratio of the epoxy resin, the flame retardant, the anhydrous ethanol and the water is 5:(1-4):(25-50):(25-100).

4. The sizing agent according to claim 3, characterized in that The epoxy equivalent of the epoxy resin is 100-250 g / eq., and the viscosity at 25° C. is 1500-20000 mPa·s; Preferably, the epoxy resin is selected from at least one of bisphenol A epoxy resin, bisphenol F epoxy resin and novolac epoxy resin.

5. The sizing agent according to claim 3 or 4, characterized in that The flame retardant is a halogen-free flame retardant; Preferably, the flame retardant is selected from at least one of phosphazene flame retardants, alkyl phosphinates, phosphaphenanthrene, phosphates, phosphates, organosilicon compounds, metal oxides, metal hydroxides and graphite substances, preferably selected from at least one of ammonium hydrogen phosphate, ammonium polyphosphate, boric acid, ammonium molybdate, polydiphenoxyphosphazene, hexaphenoxycyclotriphosphazene, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, phosphaphenanthrene triazine compounds, 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, triphenyl phosphate, resorcinol bis(diphenyl) phosphate, and toluene diphenyl phosphate.

6. The sizing agent according to any one of claims 1 to 5, characterized in that The mass ratio of polyvinyl alcohol to water contained in the polyvinyl alcohol aqueous solution is 1:(20-50); And / or, the curing agent is selected from at least one of modified imidazole, aromatic amine curing agent and aliphatic amine curing agent, preferably modified imidazole.

7. A method for preparing a sizing agent, characterized in that: The method comprises the steps of mixing a flame retardant epoxy resin emulsion, a polyvinyl alcohol aqueous solution, a modified nano silica sol and a curing agent, and then performing a first stirring to obtain the sizing agent.

8. The method according to claim 7, characterized in that The first stirring conditions include a stirring temperature of 80-120° C., a stirring time of 1-3 h, and a stirring rate of 200-500 rpm.

9. The method according to claim 7 or 8, characterized in that: The preparation method of the flame retardant epoxy resin emulsion comprises: Evenly mixing epoxy resin, flame retardant, anhydrous ethanol and water to obtain the flame retardant epoxy resin emulsion; Preferably, the epoxy resin comprises E51 epoxy resin and R170 epoxy resin, and the mass ratio of the E51 epoxy resin to the R170 epoxy resin is 4-1:1; Preferably, the mass ratio of the epoxy resin to the flame retardant is 5:1-4; Preferably, the mass ratio of the epoxy resin to anhydrous ethanol is 1:5-10; Preferably, the mass ratio of the epoxy resin to water is 1:5-20.

10. The method according to any one of claims 7 to 9, characterized in that: The preparation method of the modified nano silica sol comprises: (1) mixing ethyl orthosilicate and ethanol uniformly, stirring and drying to obtain nano silicon dioxide powder; (2) The nano-silica powder and ethanol are uniformly mixed, a silane coupling agent is added, and the mixture is stirred for a third time to obtain a modified nano-silica sol.

11. The method according to claim 10, characterized in that In step (1), the mass ratio of tetraethyl orthosilicate to ethanol is 1:8-15; And / or, the second stirring conditions include: stirring temperature of 20-80°C, stirring time of 0.1-8h, stirring rate of 200-500rpm; And / or, the mass ratio of the nano-silicon dioxide powder, ethanol and silane coupling agent in step (2) is 1:(8-15):(0.01-0.1); And / or, the third stirring conditions include: stirring temperature of 20-80° C., stirring time of 0.1-8 h, stirring rate of 200-600 rpm; And / or, the silane coupling agent in step (2) is selected from at least one of KH550, KH560 and KH570.

12. A sized carbon fiber, characterized in that: The sized carbon fiber contains the sizing agent described in claims 1-6 or the sizing agent prepared by the method described in any one of claims 7-11.

13. A carbon fiber composite material, characterized in that: The composite material contains the carbon fiber according to claim 12 and a flame retardant resin.

14. The composite material according to claim 13, characterized in that The interlaminar shear strength of the composite material is 74.6-79.2 MPa, and the tensile property is 1905.7-2021.5 MPa.

Citation Information

Patent Citations

  • Novel nano water-borne epoxy resin sizing agent for carbon fibers and preparation method thereof

    CN105040444A

  • Efficient anti-corrosion flame-retardant epoxy graphene coating material and preparation method thereof

    CN110982372A

  • Special sizing agent for moisture-proof epoxy resin-based carbon fiber composite material and preparation method thereof

    CN116024817A

  • Fire retardant epoxy resin

    US20220056261A1